Pharmacokinetic interactions between artesunate-mefloquine and ritonavir-boosted lopinavir in healthy Thai adults. (December 2015) - Rattanapunya, Siwalee; Cressey, Tim; Rueangweerayut, Ronnatrai; Tawon, Yardpiroon; Kongjam, Panida; Na-Bangchang, Kesara
Abstract Background Concomitant use of anti-malarial and antiretroviral drugs is increasingly frequent in malaria and HIV endemic regions. The aim of the study was to investigate the pharmacokinetic interaction between the anti-malarial drugs, artesunate-mefloquine and the antiretroviral drug, lopinavir boosted with ritonavir (LPV/r). Methods The study was an open-label, three-way, sequential, cross-over, pharmacokinetic study in healthy Thai adults. Subjects received the following treatments: Period 1: standard 3-day artesunate-mefloquine combination; Period 2 (2 months wash-out): oral LPV/r 400 mg/100 mg twice a day for 14 days; and, Period 3: artesunate-mefloquine and LPV/r twice a day for 3 days. Sixteen subjects (eight females) were enrolled and pharmacokinetic parameters were determined by non-compartmental analysis. Results In the presence of LPV/r, artesunate Cmax and systemic exposure were significantly increased by 45–80 %, while the metabolic ratio of dihydroartemisinin to artesunate was significantly reduced by 72 %. In addition, mefloquine Cmax and systemic exposure were significantly reduced by 19–37 %. In the presence of artesunate-mefloquine, lopinavir Cmax was significantly reduced by 22 % but without significant change in systemic drug exposure. The 90 % CI of the geometric mean ratio (GMR) of AUC0−∞ and Cmax were outside the acceptable bioequivalent range for each drug. Drug treatments were generally well tolerated with no serious adverse events. Vertigo, nausea and vomiting were the most common adverse events reported. Conclusion The reduction in systemic exposure of all investigated drugs raises concerns of an increased risk of treatment failure rate in co-infected patients and should be further investigated.